Cosmic Nihilism and the Crisis of Meaning: An Islamic Response to Taslima Nasrin’s Sexboy and Bill Bryson’s A Short History of Nearly Everything - Md Maruf Hasan; Faruque Hossain; Salahuddin (LECTURES: Journal of Islamic and Education Studies, 2026)
Cosmic nihilism offers no intrinsic meaning of human life in the vastness and emptiness of the cosmic ocean. The concept of God/Allah was merely a delusion in the brain of homo sapience. There is no divine truth outside the human brain since our brain is merely a belief-making machine. The trend of New Atheism is quite noticeable since the 9/11 attacks. Every religious belief is under scrutiny till now. When the world religions fail drastically to satisfy skeptical youth minds around the world, Can Islam show any signature for the existence of any transcendental reality? This research will use qualitative methodology. The textual and content analysis will be done from Taslima Nasrin’s fictional work ‘Sexboy’ and Bill Bryson’s non-fictional work, ‘A Short History of Nearly Everything’. Then, this research would try to look for some content from Islamic literature against the tragedy of God that the scientific worldview is trying to convince the global youth. This research is important because there was no response from Islamic perspective on these two important nihilistic works of Nasrin and Bryson. This research would suggest that Muslim intellectuals should develop Islamic thought based on a fresh interpretation of the Quran to encounter the scientific worldview that New Atheist writers are trying to advocate for global youth in the 21st century.